Application of matrix teaching materials using a problem based learning approach in increasing students' ability to understand mathematical concepts - Rohman, Wahyu; Nindiasari, Hepsi (Desimal: Jurnal Matematika, 2024)
Efforts to improve the quality of education continue to be carried out comprehensively, including aspects of knowledge, skills, attitudes, and values. Mathematics learning is understanding mathematical concepts when solving a problem. Therefore, whether or not mathematics learning has been achieved can be demonstrated if students can understand and master a given concept. This research aims to determine the increase in students' ability to understand concepts using teaching materials with a problem-based learning approach. This research used one class with 36 students. Data collection uses observation and tests. The pretest and posttest results show that the posttest results are better, namely having 10.417 points more than the pretest results. The results of the t-test analysis show a significance of 0.000. After being tested, it can be concluded that teaching materials using a problem-based learning approach are effective in improving students' ability to understand mathematical concepts.